Performance of Shariah-Compliant Indices in London and NY Stock Markets and their potential for diversification. (3rd November 2009) - Kok, Seng; Giorgioni, Gianluigi; Laws, Jason
This paper aims to contribute to the empirical literature on the performance of Sharia-Compliant Indices (SCIs) by evaluating the performance of a number of SCIs, in comparison to similar mainstream indices, as well as in comparison to other ethical funds. Furthermore, the paper will test for co-integration among the SCIs and the mainstream ones to establish whether there is any scope for diversification. The main findings are that SCIs offer an opportunity for portfolio diversification with mainstream indices and other ethical funds within the UK.